Pengembangan Potensi Wisata Embung Sumberagung Melalui Revitalisasi Atraksi Wisata - Alyaa’ Chiquita Fairuzara A. R.; Kezia Angelin Patricia; Nathania Trixie Aryanti (jurnal ABDIMAS Indonesia, 2023)
The problem faced by the village community is the lack of knowledge about the existing tourism potential, this causes the existing tourism potential to not develop and causes the environment around this tourism potential to be neglected. Because the community lacks concern for existing tourism potential because there is no attraction from tourism potential so that village communities to promote existing tourism potential are lacking. Making tourist attractions in the form of photo spots as a form of tourism village development, is carried out using the participation and socialization approach to the community, through the creation of photo spots which were inaugurated during the "Mlaku Together, Healthy Together" Walk activity. This activity was created as a forum to gather the community, village government, and stakeholders on the Embung Sumberagung tourist attraction. The implementation of developing the tourism potential of the Sumberagung Reservoir began with conducting a survey of the Embung tourist attractions to find out what attractions could be placed in the tourist area, through the survey that had been conducted it was decided that the tourist attraction that could be placed in the Embung area was a Photo Spot. After it was decided to make a photo spot to fulfill the tourist attraction, permission was then given to village officials regarding this photo spot. Revitalization was carried out by adding a photo spot area, installing a sign system, and making trash cans in the area around the reservoir. Photo spots are made with bamboo frames and have a background in the form of a pond view. The sign system is made using wood and iron materials, as a pointer to the location of the reservoir and also as a marker to help maintain environmental cleanliness.